2005
DOI: 10.1097/00003446-200502000-00005
|View full text |Cite
|
Sign up to set email alerts
|

Reception of Environmental Sounds Through Cochlear Implants

Abstract: Temporal-envelope cues appear to play a large role in the identification of environmental sounds through cochlear implants. The finer distinctions made by the HP group compared with the LP group may be related to a better ability both to resolve temporal differences and to use gross spectral cues. These findings are qualitatively consistent with patterns of confusions observed in the reception of speech segments through cochlear implants.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

12
69
1
3

Year Published

2009
2009
2022
2022

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 47 publications
(85 citation statements)
references
References 28 publications
12
69
1
3
Order By: Relevance
“…Similar to Reed and Delhorne (2005) this study also found no correlation between speech perception scores and scores on ESTs. Also error pattern analyses in both studies showed the importance of temporal characteristics in the identification of environmental sounds for CI users.…”
Section: Comparison To Reed and Delhorne's (2005) Studysupporting
confidence: 75%
See 4 more Smart Citations
“…Similar to Reed and Delhorne (2005) this study also found no correlation between speech perception scores and scores on ESTs. Also error pattern analyses in both studies showed the importance of temporal characteristics in the identification of environmental sounds for CI users.…”
Section: Comparison To Reed and Delhorne's (2005) Studysupporting
confidence: 75%
“…Despite the use of different speech and EST materials (differences in the actual sound categories and the number of stimuli in each of the categories), and the inclusion of participants with different types of CI, it is worthwhile comparing the findings from the experienced CI group in this study to those from the study by Reed and Delhorne (2005). Similar to Reed and Delhorne (2005) this study also found no correlation between speech perception scores and scores on ESTs.…”
Section: Comparison To Reed and Delhorne's (2005) Studymentioning
confidence: 68%
See 3 more Smart Citations